The Conceptual Foundations of Macroprudential Policy : A Roadmap - de la Torre, Augusto; Ize, Alain (World Bank, Washington, DC, 2013)
This paper explores post-Lehman macroprudential regulation by interacting two types of market failures (principal-agent and collective action) with two cognition modes (unconstrained and constrained) in the context of aggregate risk. Four paradigms with orthogonal policy justifications are identified. In the first time consistency paradigm, regulation offsets the moral hazard implications of efficient but time inconsistent post-crisis bailouts. In the second dynamic alignment paradigm, it protects unsophisticated market participants by maintaining principal-agent incentives continuously aligned in the face of aggregate shocks. In the third collective action paradigm, regulation arises in response to the socially inefficient yet rational financial instability resulting from uninternalized externalities. The fourth collective cognition paradigm is grounded on the need to temper the mood swings that arise from bounded rationality or severe cognitive frictions in a rapidly changing, complex and uncertain world. These four rationales give rise to important tensions and trade-offs in the design of macroprudential policy.